Mal y Belleza en la Summa Halensis: ¿cooperación u oposición? - Hugo Costarelli Brandi (Franciscanum, 2020)
The philosophical scoping often observes that both ugliness and evil have no entity and therefore can only be thought as diminished beauty and goodness. However, this diminishing entitlement is not only a lack, but may also bring about the possibility of greater beauty and goodness. In this sense, thinking about the beauty of evil has not been for many ancient and medieval authors a logical impossibility, but on the contrary a new way of speaking about the Beauty of the Universe. For many ancient and medieval authors, thinking of the beauty of evil has not been a logical impossibility, but on the contrary, a new way of speaking of the Beauty of the Universe. This has been the Augustinian and Dionysian approach, and it is also the one assumed by the well-known Summa Halensis, although from a perspective whose originality lies in the integration of these traditions. The intention of the present work is to analyze how the Summa Halensis understands that beauty is capable of integrating evil.